Effects of Media Combination and Fertilization Frequency on Growth and Yield of Pakcoy - Afifah Farida Jufri; Amrul Jihadi; Anjar Pranggawan Azhari; Dwi Noorma Putri (Gontor Agrotech Science Journal, 2023)
The demand for pakcoy continues to increase as more people must be aware of their nutritional needs. One important factor in pakcoy cultivation is the use of planting media. The main objective was to find out the best media combination and frequency to apply fertilizers for efficiency in intensive growing. The research was conducted in Cikabayan, IPB Bogor using RAL Factorial with six treatment combination and three replications. The first factor was media combination (rice husk, cocopeat, and compost), while the second factor was fertilization frequency (every week and every two weeks). Parameters observation consists of vegetative growth (plant height, number of leaves wide and length of leaves, and width of the stump) and plant production (wet weight and weight suitable for consumption). Research results indicated that planting media combination of rice husk and compost (1:1) gave a better result than other treatments in increasing leaf length (11.36 cm) and wet weight (47.12 grams). The frequency of application of foliar fertilizer had no different effect on pakcoy growth and yield and no interaction significantly between media combination and fertilization frequency.